Phylogeny and taxonomic revision of the genus Euryomma Stein (Diptera: Calyptratae: Fanniidae) - Dominguez, Martha Cecilia (2017)
We propose the first phylogenetic hypothesis for the genus Euryomma based on a cladistic analysis using characters from male adult external morphology and male and female terminalia. The genus Euryomma, to which nine new species have recently been added from Colombia and Costa rica, is revised. The cladistic analyses performed with using implied weighting and tree that shows the genus as a monophyletic group, but relationships among species show little support. Illustrations of the male genitalia have been added to the Stein?s descriptions of E. rufifrons, E. longicorne and E. nigrifemur. Euryomma erythrogaster Séguy is sinonimyzed with E. longicorne Stein. Euryomma tahami is sinonimized Eu carioca. Euryomma cornuatum is sinonymyzed with E. nigrifemur Stein, and Euryomma steni Grisales and Carvalho is synonymized with E. palpingens Wendt. New distribution records are added and a map with the known distribution of each species is provided, as well as an identification key to the males of al known species of Euryomma.